Platinum single atoms on titania aid dye photodegradation whereas platinum nanoparticles do not - Pecoraro, Claudio Maria; Sopha, Hanna; Wu, Siming; Kim, Hyesung; Wang, Yue; Macak, Jan; Santamaria, Monica; Schmuki, Patrik (Nanoscale, 2025)
The photocatalytic degradation of unwanted organic species has been investigated for decades using modified and non-modified titania nanostructures. In the present study, we investigate the co-catalytic effect of single atoms (SAs) of Pt and Pt nanoparticles on titania substrates on the degradation of the two typical photodegradation model pollutants: Acid Orange 7 (AO7) and Rhodamine B (RhB). For this, we use highly defined sputter deposited anatase layers and load them with Pt SAs at different loading densities or alternatively with Pt nanoparticles. We find that the Pt SAs have strong accelerating effects (already for a low loading density of ∼105 SAs µm−2) on the photodegradation of AO7, whereas Pt nanoparticles do hardly have an effect on the decay kinetics. The main beneficial effect of SA Pt is facilitated superoxide formation, which for SAs is significantly enhanced. Overall, the work demonstrates that Pt SA co-catalysts can have a beneficial effect not only for the well-studied use of H2 generation, but also in the photocatalytic degradation of pollutants—this is particularly the case if the degradation is dominated by a conduction band electron transfer to dissolved O2 in the solution.
CRIS-Team Scopus Importer:2025-02-28